Analysis of philosophical and ideological and cultural specificity of learning process of philological disciplines in the context of development skills of reflection (Pedagogy of Higher and Secondary Education, 2013)
Herasimova O. I. Analysis of philosophical and ideological and cultural specificity of learning process of philological disciplines in the context of development skills of reflection.The article examines the philosophical and ideological and cultural specificity of philological disciplines, it turns out, the specifics of teaching philological disciplines under pedagogical university, identifies the need for the implementation of procedural and substantive unity as components in a philological and socio-philosophical aspects.
Keywords: reflection; skills of reflection; philological discipline; self-education; educational process